Profil Kemampuan Berpikir Aljabar Siswa SMP pada Materi Volume Kubus - Titi - Rohaeti; Jajang Rahmatudin; Putri Parhati Meilani (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
The purpose of this study is to describe the students’ algebraic thinking skills and errors in solving algebraic problems on volume of cube material for class VIII of Junior High School. The research design used was in a form of the descriptive qualitative research method. This study captured the students’ algebraic thinking skill on two indicators, namely the students’ ability to represent problems in the relationship between variables and the students’ ability to perform operations on algebraic form. Based on the result of the categorization, three students from the high-level category were chosen as the subjects of this study. In depth interviews were given to the subjects of the study in order to explore the answers that they provide on the mathematic problems given. The findings revealed that the students with high-level of algebraic thinking skills could solve mathematics problem in algebraic form correctly especially in transformational activities. It was indicated by the students’ ability to provide a solution for algebraic equation problems. Meanwhile, the students’ error in solving the mathematical problems in a form of build-cube space was due to the students’ inaccuracy in writing the final results on the answer sheets for the algebraic thinking ability test. Overall, the students encountered several types of errors, those were the error in the procedural and technical/calculated on comparisons, the error in witing mathematical units, and lastly the error in substituting variables